ASIAN CHRISTIANITY: THE NEED FOR A HISTORICAL PERSPECTIVE - Brock, Sebastian P (Asian Horizons, 2016)
Any discussion of Asian Christianity needs to keep, at least in the back of the mind, the historical dimension, and the fact that Christianity is a product of Western Asia, and that in the early centuries of its history it spread East, as well as West. Unfortunately, owing to the widespread perception of the Christian tradition as having just two basic constituents, the Greek East and the Latin West, the early eastwards expansion of Christianity, which can for convenience be termed the ‘Syriac Orient,’ has all too often been forgotten. In the context of Asian Christianity it is of the greatest importance to realise that the Christian tradition is in fact tri-partite, and not just bi-partite, since the Syriac Orient constitutes the only indigenous Asian Christian tradition; moreover, it has a number of distinctive features which are of particular relevance today, both for Asian Christianity and for the other two traditions as well. Six features identified here and each briefly discussed.